The Influence of Career Paths and Incentives on Employee Performance at The Gunung Putri District Office, Bogor Regency - Julianto, Hery (Pascasarjana Universitas Primagraha, 2023)
Human resources, especially in the government sector, are vital for realizing good governance. To realize good governance, it is essential to incentives attention to employee performance. This research aims to analyze employee performance regarding incentives and career paths. The method used in this research is a quantitative method with a PLS-SEM-based causality approach, which is analyzed using the SmartPLS software tool. The sample used in this research was 35 employees. The results of this research answer entirely the proposed hypothesis, where it is partially tested that incentives and career paths can influence employee performance. Career paths also have a positive and significant impact on incentives. Likewise, incentives can mediate between career paths and employee performance positively and significantly.